Modernization of Native Healers: Implications for Health Care Delivery in Ghana - Bonsi, Stephen K. (1980)
There are two major categories of traditional healers in contemporary Ghana. The traditionalists still adhere to the basic concepts and methods of traditional healing. A significant proportion of healers have, however, adopted a new approach to healing. These new-style healers are rejecting some of the traditional beliefs about etiology of illness, and are reorganizing their medical practice. They have more education, live in cities, and acquire “modern” medical knowledge through formal training at Traditional Medical Training Centers. This new development has had a significant impact on the contributions of traditional medicine in health care delivery in Ghana.